The University of Saskatchewan : A Personal History - Thompson, Walter Palmer, 1889- (Book collections on Project MUSE., 1970)
In this memoir the author has done more than merely recount the historical facts as recorded in official documents; he goes behind the scenes to give the background of those events. He explains the reasons for decisions and actions, and examines the give and take of personal relationships and the influence of personal characteristics.